Global Financial Crisis in Effecting Asymmetrical Co-integration between Exchange Rate and Stock Indexes of South Asian Region: Application of Panel Data NARDL and ARDL Modelling Approach with Asymmetrical Granger Causility - Umaid A. Sheikh; Mosab I. Tabash; Muzaffar Asad (Cogent Business & Management, 2020)
This research examines the impact of positive and negative shocks of exchange rate on South Asian Stock indexes by employing a Non-linear Panel autoregressive distributive lag model along with a Panel Asymmetric granger casualty test. For the Panel-NARDL model, the Pre-crisis regime comprises of 289 observations from 1st January 2000 to 1st January 2008, the post-crisis regime consists of 547 observations from 1st January 2009 to May 2020 and the whole sample is constituted upon 960 observations from 1st January 2000 to May 2020. Pesaran's 2007 cross-sectional augmented IPS unit root test is also applied after estimating Pesaran's 2004 CD test. Findings indicated that the linear panel-based ARDL model failed to establish long-term cointegration between exchange rate fluctuation and stock indexes before the global financial crisis and when the overall sample period is selected. However, the asymmetrical panel-based ARDL model established a non-linear long-term association between exchange rate fluctuation and stock indexes in three regimes. Moreover in long run, when the whole sample is selected, investors reacted to only positive shocks to exchange rate and did not react to negative shocks. However, in the short run investors reacted equally to both positive and negative shocks to exchange rates. In pre-crisis and post-crisis regimes, stock indexes are only inversely related to positive shocks to exchange rate fluctuations and investors did not react to negative fluctuations in the exchange rate. However, in the short run and before the global financial crisis, investors reacted to only positive shocks to exchange rate but in the short run and after the crisis, investors did not react to positive shocks. The significance of this research is two-fold: Firstly, we have examined the reaction of investors to both positive and negative shocks to exchange rate fluctuations under three different regimes. Secondly, we have shown that non-linear panel-based modelling is more effectual in estimating asymmetrical linkages between exchange rate fluctuation and stock indexes.
Keywords: 650; non-linear panel ARDL; cross-sectional augmented IPS unit root; South Asian stock indexes; global financial crisis; asymmetric granger causality analysis; exchange rate and stock prices